Egyptian diatomite as high fluid loss squeeze slurry in sealing fractures and - A.M. Al-Sabagh; A.A. El-Awamri; M.I. Abdou; H.A. Hussien; H.M. Abd El Fatah; W.E. Rasmy (Egyptian Journal of Petroleum)
Lost circulation is the most costly mud related drilling problem, and induced fracture. Water slurry of diatomite is used as the high fluid loss squeeze slurry in the treatment of lost circulation and in decreasing fluid loss. Egypt has diatomite deposits, especially in El-Fayuom Depression. Fourteen samples were collected from Qasr El-Sagha at the northern shore of Birket Qarun. Samples were examined to identify the diatom species then subjected to X-ray fluorescence, XRD and grain size distribution tests. A total of 38 species related to 13 diatom genera were identified. Cocconeis, Epithemia and Rhopalodia were the predominant genera. The diatomaceous earth which acts as a filter aid material was tested with different additives; bentonite, lime, finely divided paper, polymer, barite and different concentrations with different types of lost circulation materials (LCM) to form a high fluid loss squeeze slurry. As a result the required time for collecting the filtrate was decreased to be in the range of 50 s to 1 min and 49 s comparing with the international standard which recommended the filtrate should be collected maximum within 2–3 min.